Centering Prayer as an Alternative to Mindfulness-Based Cognitive Therapy for Depression Relapse Prevention - Knabb, Joshua J. (Journal of religion and health, 2012)
In the last two decades, mindfulness has made a significant impact on Western secular psychology, as evidenced by several new treatment approaches that utilize mindfulness practices to ameliorate mental illness. Based on Buddhist teachings, mindfulness offers individuals the ability to, among other things, decenter from their thoughts and live in the present moment. As an example, mindfulness-based cognitive therapy (MBCT) teaches decentering and mindfulness techniques to adults in an eight-session group therapy format so as to reduce the likelihood of depression relapse. Yet, some Christian adults may prefer to turn to their own religious heritage, rather than the Buddhist tradition, in order to stave off depression relapse. Thus, the purpose of this article is to present centering prayer, a form of Christian meditation that is rooted in Catholic mysticism, as an alternative treatment for preventing depression relapse in adults. I argue that centering prayer overlaps considerably with MBCT, which makes it a suitable treatment alternative for many Christians in remission from depressive episodes.